Application Of Liquid Organic Fartilizer From Banana Weevils On The Growth Yield Of Mustard Greens - Yasmar Daniel Manurung; Novilda Elizabeth Mustamu; Widya Lestari (Green Publisher Indonesia, 2024)
This research was conducted in the Courtyard of the Tebing Tinggi Pangkatan Village Post in Labuhanbatu Regency, North Sumatra Province, from November 2022 to January 2023. The study utilized a Completely Randomized Design (CRD) with 3 replications and 1 treatment factor, which was the dosage of liquid organic fertilizer. Based on the results of the 35-day study on the application of Liquid Organic Fertilizer (LOF) to sweet mustard plants (Bransisca Juncea L), it was found that the highest dosage, which was 185 ml, significantly differed from the control group where no LOF was applied. Meanwhile, the growth with dosages of 90 ml, 100 ml, and 150 ml showed significant differences compared to the control group.